2019
DOI: 10.3390/chemosensors7040062
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Microflowers Grown by Chemical Bath Deposition: A Low-Cost Approach for Massive Production of Functional Nanostructures

Abstract: The massive production of nanostructures with controlled features and high surface area is a challenging and timely task in view of developing effective materials for sensing and catalysis. Herein, functional ZnO nanostructures, named microflowers (MFs) have been prepared by a facile and rapid chemical bath deposition. ZnO MFs show an intriguing sheets-composed spheroidal shape, with diameters in the range 0.2–2.5 µm, whose formation is achieved by a complexing action by F in an aqueous solution of zinc nitrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…In the PL spectra of the ZnO NCs, a narrow near-band edge emission (NBE) around 380 nm and a broad band deep-level emission (DLE) between 450 nm to 700 nm were generally observed [5][6][7][8]27]. Figure 3 shows the spectra normalized to the absorbance at λex = 290 nm.…”
Section: Photoluminescence (Pl)mentioning
confidence: 99%
See 2 more Smart Citations
“…In the PL spectra of the ZnO NCs, a narrow near-band edge emission (NBE) around 380 nm and a broad band deep-level emission (DLE) between 450 nm to 700 nm were generally observed [5][6][7][8]27]. Figure 3 shows the spectra normalized to the absorbance at λex = 290 nm.…”
Section: Photoluminescence (Pl)mentioning
confidence: 99%
“…The stronger suppression of the NBE band compared to the DLE band most likely indicated that RE ions acted as non-radiative defects, the origin of which was different from the radiative defects responsible for the DLE band. In the PL spectra of the ZnO NCs, a narrow near-band edge emission (NBE) around 380 nm and a broad band deep-level emission (DLE) between 450 nm to 700 nm were generally observed [5][6][7][8]27]. Figure 3 shows the spectra normalized to the absorbance at λ ex = 290 nm.…”
Section: Photoluminescence (Pl)mentioning
confidence: 99%
See 1 more Smart Citation
“…ZnO nanostars (NSs) were synthesized by means of chemical bath deposition (CBD). Starting from an aqueous solution of zinc nitrate and hexamethylenetetramine (HMTA) [ 34 ], the ZnO NSs production was attained by adding ammonium fluoride to the bath [ 26 ]. Three solutions (50 mL each) were separately prepared with deionized water (MilliQ, 18 MΩ cm): (i) 25 mM zinc nitrate hexahydrate ( , purum p.a., crystallized, ≥99.5%, Sigma Aldrich, Milan, Italy); (ii) 25 mM HMTA ( ≥ 99.5%, Sigma Aldrich, Milan, Italy); and (iii) 16 mM ammonium fluoride ( , ≥99.99%, Sigma-Aldrich, Milan, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…Owing to its eco-friendly nature and good electrochemical activity, ZnO also became a promising electrode material for supercapacitors [ 19 , 20 , 21 ]. Moreover, ZnO can be easily nanostructured in a multitude of morphologies by employing many different methods [ 22 , 23 , 24 , 25 , 26 ]. Solution routes for ZnO nanostructure synthesis have a multitude of advantages, such as cost containment, a simple laboratory setup, low-temperature processes, and fast kinetics growth [ 27 ].…”
Section: Introductionmentioning
confidence: 99%